Inotrope Use and Intensive Care Unit Mortality in Patients With Cardiogenic Shock: An Analysis of a Large Electronic Intensive Care Unit Database - Gao, Fei; Zhang, Yun (Frontiers in Cardiovascular Medicine, 2021)
Abstract Purpose: To determine whether inotrope administration is associated with increased all-cause mortality in cardiogenic shock (CS) patients and to identify inotropes superior for improving mortality. Method: This retrospective cohort study analysed data retrieved from the Philips Electronic ICU (eICU) database, a clinical database of 200,859 patients from over 208 hospitals located throughout the United States. The database was searched for patients admitted with CS to the intensive care unit (ICU) between 2014 and 2015. We evaluated 34,381 CS patients. They were classified into the inotrope and non-inotrope groups based on whether inotropes were administered during hospitalization. The primary endpoint was all-cause hospital mortality. Findings: In total, 15,021 (43.69%) patients received inotropes during hospitalization. The in-hospital mortality rate was significantly higher in the inotrope group than in the non-inotrope group (2999 [24.03%] vs. 1547 [12.40%], adjusted hazard ratio: 2.24; 95% confidence interval [CI]: 2.09-2.39; p<0.0001). After propensity score matching according to the cardiac index, 359 patients were included in each group. The risk of ICU (OR 5.65, 95% CI, 3.17-10.08, p<0.001) and hospital (OR 2.63, 95% CI: 1.75-3.95, p<0.001) mortality in the inotrope group was significantly higher. In the inotrope group, the administration of norepinephrine ≤0.1 μg/kg/min and dopamine ≤15 μg/kg/min did not increase the risk of hospital mortality, and milrinone administration was associated with a lower mortality risk (odds ratio: 0.559, 95% CI: 0.430-0.727, p<0.001). Meanwhile, the administration of >0.1 μg/kg/min dobutamine, epinephrine, and norepinephrine and dopamine >15 μg/kg/min was associated with a higher risk of hospital mortality. Conclusions: Inotropes should be used cautiously because they may be associated with a higher risk of mortality in CS patients. Low-dose norepinephrine and milrinone may associated with lower risk of hospital mortality in these patients, and supportive therapies should be considered when high-dose inotropes are administered.